Treatment results of microdissection testicular sperm extraction - Klami, Rauni (fi=Turun yliopisto|en=University of Turku|, 2024)
Azoospermia is defined by a complete absence of sperm in repeated semen analyses. In non-obstructive azoospermia (NOA) sperm production in the testicles is severely impaired or completely absent. Sperm can be recovered in approximately half of the men with NOA by microdissection testicular sperm extraction (MD-TESE), and many of these men can father biological children with intracytoplasmic sperm injection (ICSI) (Corona et al. 2019). Assisted reproduction techniques (ART) using these sperm seem to be as effective as other treatments performed for moderate or severe male infertility (Ravizzini et al. 2008). Predicting sperm recovery and the ICSI treatment results for an individual with NOA remains difficult, and refraining from offering the treatment is rarely relevant (Enatsu et al. 2016). In Finland, MD-TESE operations were started in 2008 at Turku University Hospital (Tyks). From the first 100 operations, information was collected on the patients' diagnoses, previous procedures to find sperm, and the results and adverse effects of the operations. Sperm were found in 42 men. ICSI treatments with MD-TESE sperm and other ICSI treatments for moderate or severe male infertility in Tyks were compared, and the treatment results were similar in terms of fertilization, clinical pregnancy rate, live birth rate, gestational age at delivery and birth weight of the children born after ICSI. In the magnetic resonance imaging (MRI) of the testicles, the apparent diffusion coefficient (ADC) value, which reflects the metabolism of the tissue, can be measured (Tsili et al. 2018). Twenty-one men presenting for MD-TESE and ten fertile control men MRI of the pelvis, and testicular ADC values were compared in different diagnostic groups and in relation to sperm retrieval. There were no significant differences in ADC values in relation to sperm retrieval success in MD-TESE or between different diagnosis groups, but ADC values in healthy controls were significantly lower than in men with NOA. This study found that MD-TESE is an effective way to recover sperm and achieve biological parenthood for men with NOA, but for more than half of the men, no sperm production exists in the testis to enable successful sperm recovery. New methods of predicting sperm recovery are needed to avoid unnecessary operations.

Kiveksen mikrodissektioleikkauksen hoitotulokset Azoospermia tarkoittaa siittiöiden täydellistä puuttumista toistetuissa siemennesteanalyyseissa. Non-obstruktiivisessa azoospermiassa (NOA) kivesten siittiötuotanto on erittäin vähäistä tai puuttuu kokonaan. Hiukan alle puolelta miehistä on NOA-tilanteessakin löydettävissä siittiöitä kiveksen mikrodissektioleikkauksella (MD-TESE), ja moni heistä voi saada biologisia jälkeläisiä mikroinjektiohoidolla (ICSI) (Corona et al. 2019). Hedelmöityshoidot vaikuttavat yhtä tehokkailta kuin muutkin miehen kohtalaisen tai vaikean lapsettomuuden vuoksi tehdyt hoidot (Ravizzini et al. 2008). Siittiöiden löytymisen ja hedelmöityshoidon tulosten ennustaminen yksittäisen miehen NOA-tilanteessa on vaikeaa, ja hoidosta pidättäytyminen on siksi vain harvoin perusteltua (Enatsu et al. 2016). Suomessa MD-TESE-leikkaukset aloitetiin vuonna 2008 Turun yliopistollisessa keskussairaalassa (Tyks). Sadasta ensimmäisestä leikkauksesta kerättiin tiedot potilaiden diagnooseista, edeltävistä toimenpiteistä siittiöiden löytämiseksi sekä leikkausten tuloksista ja haittavaikutuksista. Verrattaessa MD-TESE-siittiöillä Tyksissä tehtyjä ICSI-hoitoja muihin miehen kohtalaisen tai vaikean lapsettomuuden vuoksi tehtyihin ICSI-hoitoihin, hoitotulokset olivat samanlaiset. Kivesten magneettitutkimuksessa (MRI) voidaan mitata kudoksen aineenvaihduntaa kuvastava apparent diffusion coefficient -arvo (ADC) (Tsili et al. 2017). 21 MD-TESE-leikkaukseen saapuvalle miehelle ja kymmenelle hedelmälliselle verrokkimiehelle tehtiin lantion magneettikuvaus (MRI), ja kivesten ADC-arvoja verrattiin eri diagnoosiryhmissä ja suhteessa siittiöiden löytymiseen. ADC-arvoissa ei ollut eroja suhteessa siittiöiden löytymiseen MD-TESE-leikkauksessa eikä diagnoosiryhmien välillä, mutta verrokkien ADC-arvot olivat matalampia kuin miesten, joilla oli NOA. Tutkimus osoitti, että MD-TESE on tehokas tapa löytää siittiöitä ja saavuttaa biologinen vanhemmuus NOA-tilanteessa, mutta yli puolelta leikkaukseen tulevista miehistä ei löydy kiveksestä siittiötuotantoa. Uusia menetelmiä siittiöiden löytymisen ennustamiseen tarvitaan, jotta vältyttäisiin turhilta leikkauksilta.